A balanced salt solution that prevents agglomeration of nano iron oxo-hydroxides in serum-free cellular assays. (9th January 2015) - Pereira, Dora I A; Lederer, Bianca; Powell, Jonathan J
Abstract: Nano iron oxo-hydroxides have numerous and increasing applications in biology and medicine. Assessment of their uptake and toxicity often requires cell culture but maintaining iron oxides uniformly nano-dispersed in such conditions can be challenging. We describe a balanced salt solution (BSS) compatible with cellular assays for use in such investigations. We determined hydrodynamic particle size and dispersibility of nano iron in BSS. The BSS, containing 130 mM NaCl, 10 mM KCl, 1 mM MgSO4, 5 mM glucose and 1.8 mM CaCl2 in 10 mM PIPES buffer (pH 7.4), was capable of maintaining nanoparticulate tartrate-modified Fe(III) oxo-hydroxide (i.e. nano Fe) mono-disperse (≥95% nanoparticulate) with a mean hydrodynamic particle diameter of 6.1 ± 0.3 nm. This size was similar to the native form of the nano Fe material (i.e. as synthesized) with a mean hydrodynamic particle diameter of 4.3 ± 0.1 nm in water. Furthermore, we show that BSS also adequately maintains nano Fe dispersion when supplemented with inhibitors of particle uptake or lysosomal acidification, namely chloropromazine and monensin, and when used at pHs 6.5 or 5.8. In conclusion, we provide a method for nanodispersion of iron oxo-hydroxides that is suitable for short term (1–3 h) cellular exposure investigations.